Theorising the interaction of caste, class and gender: A feminist sociological approach. (October 2016) - Velaskar, Padma
In the context of the rise of feminist scholarship exploring links between caste, class and gender, the particular concern of this article is with developing a sociological framework that would help locate gendered power relations and women's oppression within the structures of caste and class domination, inequality and social stratification. While a politics of difference is indispensable to highlight the differential axes and experiences of oppression, a critical sociological understanding of social relations that make for structural differences and commonalities needs to be built up in order to grapple with a complex and rapidly changing social reality. Drawing from multiple critical perspectives to create a conceptual synthesis and taking a structural approach to 'difference', the article develops the contours of a critical feminist sociological framework grounded in theories of production relations and cultural subordination that may be useful to explore the complex and dynamic interconnections between caste, class and patriarchy. It also attempts to understand aspects of caste–class-specific gender relations and patriarchal forms as well as account for key differences and divisions between women. The article argues that by providing a contextualised, interactional understanding of differential social relations and differential social locations of both women and men, feminist sociology can make a new and distinct contribution to the systematic and systemic study of, as well as illuminate more fully, the workings of societal systems of domination–subordination.